HUBUNGAN KECERDASAN SPIRITUAL DENGAN PERILAKU MENYIMPANG - Mulyati, Sri; Hamidah, Nur; Bassar, Agus Samsul (THORIQOTUNA: Jurnal Pendidikan Islam, 2022)
This study aims to determine the relationship between students' spiritual intelligence and awareness of avoiding deviant behavior in Serba Bakti Suryalaya Islamic Junior High School students. The method used in this study is a descriptive method with a quantitative approach, namely a research method that is shown to describe existing phenomena, currently taking place, or in the past. The results of this study indicate that the relationship between spiritual intelligence and deviant behavior in students of SMP Islam Serba Bakti Suryalaya there is a significant positive correlation with the result of "r" count 0.624, which when viewed in the interpretation table of the "r" value, it is known that the correlation between the two the variable is in the range between 0.40-0.70, which means that between the X variable and the Y variable, namely between spiritual intelligence and students' awareness of avoiding deviant behavior, there is indeed a moderate/sufficient correlation